Karakterisasi Fisiologi Cendawan Entomopatogen Lecanicillium lecanii sebagai Calon Bahan Aktif Bioinsektisida untuk Pengendalian Telur Kepik Coklat (Riptortus linearis) pada Kedelai - Yusmani Prayogo (Buletin Plasma Nutfah, 2013)
The aimof the research was to determine the physiological charactersof various L. lecanii isolates as active materials ofbioinsecticide to control pod sucking bug Riptortus linearisegg on soybean. Thirty seven (37) of L. lecanii isolates werecollected from four locations of soybean plantation inIndonesia. This study obtained four virulent isolates that werepotential as active ingredient of bioinsecticide i.e. Ll-JTM11,Ll-JTM12, Ll-JTM15, and Ll-TB2. Virulent isolates wereobtained from insect cadaver isolation in the field, while lessvirulent isolates were gained from soil. Physiologicalcharacters of potential isolates were fast colonization rate ofthe egg, thick and wholly, high sporulation with large conidialsize, high germination rate after 12 hours incubated in thewater, up to 95% germ tubes were formed. Clustering ofisolates based on the physiology character can determine thefungus virulence, while the grouping based on the source orhost location can not select fungal virulence. The virulentisolates had similarity in physiological characters equal to98%. Therefore, four potential isolates could be used asbiological agents in integrated pest mangement program(IPM), especially pod sucking bug R. linearis on soybean.